Cooperative space‐time block coded full‐duplex relaying over frequency‐selective channel. Issue 7 (1st May 2015) - Jeon, Sungho; Han, Jae‐Shin; Choi, Jeong‐Min; Seo, Jong‐Soo
Abstract : In this study, the authors investigate a distributed time‐reversal space‐time block coded (D‐TR‐STBC) system with amplify‐and‐forward full duplex relaying (FDR) over frequency‐selective channel. In the first, they present an FDR to use in a cooperative D‐STBC relaying in which a relay transmits the delayed signal as much as one frame in order to maintain the orthogonal property of STBC at the destination. Then, they briefly present the conventional full self‐interference cancellation (SIC) which continuously removes the self‐interference signal. As an alternative to the full SIC, they further introduce a partial SIC that periodically performs the SIC process. As a result, it can reduce cancellation processing by a half time compared to the full SIC. In the second, they propose the efficient and yet optimal destination structure consisting of the forward interference cancellation (IC), backward IC and joint equalisation and data combining in order to obtain a full coding gain. It is shown that the proposed D‐TR‐STBC‐FDR system has ∼3 dB signal‐to‐noise ratio gain compared to cooperative half‐duplex relaying with D‐TR‐STBC while it has the same diversity order. In addition, they show that there are no performance losses between FDR with full SIC and FDR with partial SIC.